Basic Area Navigation (B-RNAY) - Franjković, Davor; Bucak, Tino; Martek, Maja (Promet - Traffic&Transportation, 2012)
As a subprogram of wider area navigation, the basic areanavigation defines operations within the European airspace inthe ATS route netlvork, and terminal controlled areas, accordingto the developed chronology of gradual implementationand clearly defined authorities regarding its implementation.The introduction of the basic area navigation operations intothe airspace of the European Civil Aviation Conference, has resulteddirectly from a significant growth of traffic density andthe impossibility of control using conventional methods. It willinsure numerous advantages, first of all greater traffic throughputcompared to the previous method of navigation guidance,thereby not disturbing the existing safety standards.